Risk assessment of cognitive development of early childhood children in quarantine days: a new AHP approach - Kirişci, Murat; Topaç, Nihat; Bardak, Musa; Bardak, Musa (Murat TOSUN, 2020)
The world is faced with disasters caused by natural or human effects from time to time. The various political, economic, health, and social consequences of these disasters affect people for different periods of time. In natural disasters and especially in epidemic diseases, some measures are taken to protect people from the negative effects of the situation. One of the measures that can be taken is quarantine. The target audience of this study is children aged 5-6 in the early childhood. Children of this age group are in the process of gaining skills in expressing their feelings during this period. In addition, the emotional responses of these children can be noticed by a careful observer or even an expert. The purpose of this study is to evaluate the risks of the effects of quarantine status related to COVID-19 pandemic on cognition and behavior of children staying at home. A new AHP technique was used to assess the risks of the quarantine process in early childhood children.
Keywords: COVID-19; Early childhood; Risk assessment; Pythagorean fuzzy set; Analytic hierarchy process; Cognitive development; Behavioural development